Risk pricing strategies for public-private partnership projects - Boussabaine, Halim A. (Chichester, West Sussex : Wiley Blackwell, 2014)
'The book provides up-to-date coverage of the latest developments in risk pricing strategies and presents a comprehensive treatment of the methodologies involved in designing and building risk pricing models.The author explains how public-private partnership project risk is priced and appreciated by means of the correct application of innovative risk modelling techniques, where the emphasis is risk pricing strategies as well as price evaluation methods. Risk pricing is covered as an integral part of the PPP projects procurement process - from the perspectives of both private and public stakeholders.This book sets out the key principle strategies involved in risk pricing of PPP projects in a clear and accessible way and provides the reader with fundamental principles of risk pricing theories and enveloping processes. Each chapter treats specific aspects of risk in PPP projects, including: PPP process map Project risk management strategies Project risk measurement and modelling Strategies for risk pricing Risk pricing at each of the project life cycle stages Pricing project finance risks The first two aspects provide the required background knowledge with which to conceptualise the main elements of risk management in the context of PPP procurement systems. Project risk measurement in then introduced with modelling methods that might be applicable in the process of risk pricing PPP projects. This is followed by a comprehensive introduction to an innovative framework for risk pricing of PPP projects. Finally, the book addressed risk pricing at each stage of PPP projects development and operation.A thematic structure is used, dealing with all the important risk pricing issues, and relevant real-world situations are analysed through case study examples'--
'This book sets out the key principle strategies involved in risk pricing of PPP projects in a clear and accessible way and provides the reader with fundamental principles of risk pricing theories and enveloping processes'--
Machine generated contents note: Contents Chapter 1: Mapping of the PPP process. 1.1 Introduction. 1.2 key stages in the PFI/PPP procurement process. 1.3 PPP as a driver for risk transfer for the private sector. 1.4 PPP as a driver for value for money. 1.5 Risk and value for money. 1.7 Summary. 1.8 References. Chapter 2: Project risk management strategies. 2.1 Introduction. 2.1 Types of project risk. 2.3 Project life cycle risk management plan. 2.4 The project risk management process. 2.5 Strategies for project risk management. 2.6 Risk governance. 2.7 Summary. 2.8 References. Chapter 3: Risk management in PPP projects. 3.1 Introduction. 3.2 An integrated framework for risk management of PPP projects. 3.3 Design risk management. 3.4 Construction Risk Management. 3.5 Operation risk management. 3.6 Project finance risk management. 3.7 Summary. 3.8 References. Chapter 4: Project risk measurement and modelling. 4.1 Introduction. 4.2 quantifying risks. 4.3 Risk modelling methods. 4.4 Selecting a risk modelling technique. 4.5 Building risk models. 4.6 Assessing the accuracy of risk models. 6.7 Summary. 6.8 References. Chapter 5: Strategies for risk pricing. 5.1 Introduction. 5.2 Principles of risk pricing strategies. 5.3 Risk pricing management strategies. 5.4 Value gain from risk retention. 5.5 Value loss from risk retention. 5.6 Optimum return on risk retention. 5.7 Cost of risk control. 5.8 Resources capability for risk control. 5.9 Summary. 5.10 References. Chapter 6: Pricing design risks. 6.1 Introduction. 6.2 Overview of design risks. 6.3 Strategies for mitigating and managing design risks. 6.4 Pricing design risks. 6.5 Design risks pricing example. 6.6 Summary. 6.7 References. Chapter 7: Pricing construction risks. 7.1 Introduction. 7.2 Overview of construction risks. 7.3 Strategies for mitigating and managing construction risks. 7.4 Pricing construction risks. 7.5 Construction risks pricing example. 7.6 Summary. 7.7 References. Chapter 8: Pricing operational risks. 8.1 Introduction. 8.2 Overview of operational risks. 8.3 Strategies for mitigating and managing operational design risks. 8.4 Pricing operational risks. 8.5 Operational risks pricing example. 8.6 Summary. 8.7 References. Chapter 9: Pricing project finance risks. 9.1 Introduction. 9.2 Overview of project finance. 9.3 Project finance risk map. 9.4 Strategies for pricing project finance risks. 9.5 Project finance risk price modelling. 9.6 Summary. 9.7 References.
Includes bibliographical references and index.
Keywords: Public-private sector cooperation; Risk management; Building -- Estimates